Pengembangan Aplikasi Penerimaan Peserta Didik Baru Berbabasis Zonasi - Khairil, Khairil; Zulfiandry, Ricky (UNIVED Press, 2020)
The zoning system implemented by the Ministry of Education and Culture in the process of Accepting New Students in schools aims to equalize the right to education for school-aged children. The aim of this research is to develop a Zoning-Based Application for Accepting New Students at State junior high school 6 Bengkulu City. The methods used in this research are interviews, literature study, analysis, system design, testing and implementation. The system presented is in the form of zoning data input, prospective new student scores, national exam score data, while the process menu is a process menu for determining the assessment of prospective new students. The output produced is a report on new student registration and a report on new students accepted